CHOICE OF SHORT-TERM CONSTANT CONFIGURATION OF THE DISTRIBUTION NETWORK - I. I. Golub; O. N. Voitov; E. V. Boloev; L. V. Semenova (Известия высших учебных заведений: Проблемы энергетики)
The work studies a possibility of choice for a given interval of changing the load power and the capacity of renewable generation sources of such a constant configuration of the primary distribution network, at which the energy losses differ minimally from the losses at the optimal hourly reconfiguration The study was carried out using the fast algorithm of the primary distribution network reconfiguration by the losses minimization criterion that was worked out by the authors. The algorithm efficiency is proved by comparing the results obtained on study basis with the results of other methods. After emergency cut-out of the sectionalizing switch the reconfiguration algorithm based on the methods known in the graph theory allow us to determine the line switch required for restoration. For the final choice of such switches feasibility of the post-emergency is tested and the controls are chosen, if the conditions are not met. The work of the proposed methods is demonstrated by the example of the 33 nodal IEEE scheme.